Magnetically Separable Fe3O4/SiO2/TiO2 Photocatalyst Composites Prepared through Hetero Agglomeration for the Photocatalytic Degradation of Paraquat - Gunlazuardi, Jarnuzi; Fisli, Adel; Ridwan, Ridwan; Krisnandi, Yuni Krisyuningsih; Robert, Didier (Makara Journal of Science, 2021)
A photocatalyst supported on magnetic material allows the simple technique by using an external magnetic material to separate photocatalyst from the treated water. Thus, it is a magnetically separable nanoparticles photocatalyst (MSNP). The use of superparamagnetic nanoparticles that do not pose spontaneous magnetic moment thus could be dispersed in water and can be recollected easily by an external magnetic bar. We prepare Fe3O4/SiO2/TiO2 composite by hetero agglomeration of Fe3O4/SiO2 and TiO2 at a pH range of 3 to 6.2 in an aqueous slurry.The Fe3O4/SiO2 was prepared via co-precipitation of iron (II) and iron (III) ionic solution containing ammonium hydroxide and sodium silicate. The prepared composites were characterized by XRD, TEM, FTIR, and VSM, while the photocatalytic activities were tested toward paraquat in water. Based on zeta potential values, the Fe3O4/SiO2and TiO2 were being hetero agglomerated at pH 5 to obtain Fe3O4/SiO2/TiO2 composite. The XRD characterization confirmed the presence of anatase, rutile, and magnetite crystal phases. TEM images showed that the Fe3O4 was covered by SiO2 and randomly attached to TiO2. The observed FTIR peak at 940-960 cm-1 attributed to -Si-O-Ti- bonding mode, ensuring photocatalyst (TiO2) adherence to the Fe3O4/SiO2 cluster. The prepared Fe3O4/SiO2/TiO2 composite showed good photocatalytic activity for the paraquat removal and showed a good magnetic property (VSM measurement)